Boxed up? Lunchboxes and expansive mothering outside home. (30th November 2018) - Harman, Vicki; Cappellini, Benedetta
Abstract : This article unpacks the experiences of 30 British women making lunchboxes for their children, and their opposition to opting for school dinners. Findings emerging from photo-elicitation interviews and focus group discussions show how mothers consider themselves the only social actor able to make a 'proper lunchbox'. School dinners are considered a risky option for their children, and fathers' interference in preparing lunchboxes is viewed with suspicion. The article shows how lunchboxes can be viewed as an expansion of intensive mothering: a way of making home away from home, stretching the intensive domestic care used for toddlers to school-aged children. Expansive mothering is characterised by mothers' mediating role that places them between the child and the outside world. This role is mainly performed as a risk management activity aimed at recreating the domestic security outside the home, yet it also reinforces the message that feeding children is a mother's domain.